2017
DOI: 10.1038/ejcn.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine supplementation on biomarkers of oxidative stress, antioxidant capacity and lipid profile, in patients with pemphigus vulgaris: a randomized, double-blind, placebo-controlled trial

Abstract: LC consumption may have favorable results on TAC, OSI and lipid profiles in patients with PV. The results were in line with the idea that LC supplementation can be associated with positive effects on metabolic status and OS of patients with PV.European Journal of Clinical Nutrition advance online publication, 23 August 2017; doi:10.1038/ejcn.2017.131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…This result was in agreement with MALAGUARNERA et al (2010), who found that L-carnitine ameliorated the blood glucose, TAG, cholesterol, and lipoprotein concentrations in NASH patients. Also, pemphigus valugaris patients had low levels of serum total cholesterol, TAG, and LDL-c without any change in HDL-c level, following L-carnitine administration (MOHAMMADI et al, 2018). The reduction in the serum LDL-c concentration may be attributed to the enhancement of LDL receptor expression by L-carnitine (YOUSEFINEJAD et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agreement with MALAGUARNERA et al (2010), who found that L-carnitine ameliorated the blood glucose, TAG, cholesterol, and lipoprotein concentrations in NASH patients. Also, pemphigus valugaris patients had low levels of serum total cholesterol, TAG, and LDL-c without any change in HDL-c level, following L-carnitine administration (MOHAMMADI et al, 2018). The reduction in the serum LDL-c concentration may be attributed to the enhancement of LDL receptor expression by L-carnitine (YOUSEFINEJAD et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of the studies enrolling haemodialysis patients suggests that L-carnitine supplementation may positively affect serum LDL level, although it was not associated with a significant change in serum TCh, HDL and TG levels [49]. Similarly, lipid profile improves following L-carnitine supplementation in patients with pemphigus vulgaris [50] and in women with knee osteoarthritis [51]. In the present study, significant reduction in serum TCh, LDL and TG concentrations has been observed following 24-weeks supplementation, but not attributable to L-carnitine.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…To have more detailed view, mitochondria, peroxisomes, various types of oxidases, ascorbic acid oxidation and cytochrome as well as ultraviolet/ionizing radiations, chemotherapeutics, stress, and environmental toxins can be named as sources of production of endogenous ROS [63] . Protective antioxidants enzymes can effectively decompose ROS at their mild states however; the condition can change to toxic levels if the production rate surpasses much more than the antioxidant system capacity [64] , [65] . As an example, endogenous and exogenous ROS could affect lens crystallins as of a biological target.…”
Section: Oxidative Stress Conceptmentioning
confidence: 99%